Clerk & Lindsell on torts. - Clerk, J. F. (John Frederic), 1848-1931.; Lindsell, W. H. B. (William Harry Barber), 1848-1898. (London : Sweet & Maxwell, 2020)
Clerk & Lindsell on Torts, is the definitive work and market leader in this area of law; it offers the most comprehensive coverage of the s ubject, providing the end user with indispensable access to current, fr equent and unrivalled authoritative information on all aspects of tort law. An essential reference tool, Clerk & Lindsell is widely referred t o by practitioners and cited the judiciary. The new edition brings the work completely up-to-date with the changes in the law since the last e dition in 2014, including those arising from the Defamation Act 2013 an d the developments in all of the key case law, including relevant decis ions from the Supreme Court and Court of Appeal. Supreme Court decision s include: Campbell v Peter Gordon Joiners Ltd [2016] UKSC 38 Patel v M irza [2016] UKSC 42 Rahmatullah v Ministry of Defence [2017] UKSC 1 Moh ammed v Ministry of Defence (No 2) [2017] UKSC 2 BPE Solicitors v Hughe s-Holland [2017] UKSC 21 Key features: Sets out the general principles, including liability and causation, and details the practice and proced ure of seeking solutions. Explains the general defences, such as claima nt's wrongdoing, contributory negligence, consent and assumption of ris k, exclusion of liability and miscellaneous defences Covers all areas o f tort, from joint liability and vicarious liability to capacity and pa rties, from foreign torts to negligence, from breach of statutory duty to professional liability, and from product liability and occupiers lia bility to employers liability and public service liability. Deals with important areas from malicious prosecution to wrongful interference wit h goods, from deceit to trespass of land and dispossession, from animal s liability to nuisance and Rylands v Fletcher implications, and from m alicious falsehood to economic torts Discusses statutory IP rights, pas sing off and breach of confidence and privacy. Includes a fully updated chapter on Defamation to take in the changes in law brought in with th e Defamation Act 2013 Deals extensively with damages. Covers injunction s and limitation periods Includes discussion of self-help and discharge of torts. Considers relevant human rights issues. Comprehensive commen tary on recent case law showing how the general principles apply to dif ferent situations - over 10,000 cases cited Is relevant to all common l aw countries, as it considers relevant commonwealth case law.
"Table of cases": pages xix-cccxxxviii.
"Table of statutes": pages cccxxxix-ccclxxvi.
Kept up to date with on supplements.
Includes bibliographical references and index.
Keywords: Torts -- England; Torts -- Wales